(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
The rising demand for sustainable energy sources has driven further study and development in solar energy systems. Capturing solar energy for many applications, such as space heating, water heating, and power generation, flat plate solar collectors (FPSCs) are very necessary. This work is to provide a comprehensive overview of present development and strategies used to increase the efficiency of the solar collector as well as fundamental ideas guiding the operation of (FPSC). Among the many methods examined, the use of modern materials and nanotechnology especially the inclusion of nanoparticles and nanostructured coatings has been shown to greatly improve thermal performance, therefore attaining the most increase in efficiency. The overview of these significant findings in the assessment points to topics of future investigation direction. It emphasizes the need for all-encompassing strategies that take environmental issues into account along with technical advancement to enhance performance and general use(FPSC). Academics, engineers, and legislators working toward the sustainable development of technologies will find great value in this work.